2012
DOI: 10.1016/j.ydbio.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Cdx function is required for maintenance of intestinal identity in the adult

Abstract: The homeodomain transcription factors Cdx1 and Cdx2 are expressed in the intestinal epithelium from early development, with expression persisting throughout the life of the animal. While our understanding of the function of Cdx members in intestinal development has advanced significantly, their roles in the adult intestine is relatively poorly understood. In the present study, we found that ablation of Cdx2 in the adult small intestine severely impacted villus morphology, proliferation and intestinal gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 59 publications
5
81
0
Order By: Relevance
“…40 Ablation of Cdx2 in the intestine results in a decrease of mature enterocytes, and loss of goblet, enteroendocrine and Paneth cells. 41 We showed that treatment with βHB or overexpression of ketogenic enzyme HMGCS2 increased CDX2 expression in intestinal cells. Moreover, our results showed that increased ketogenesis resulted in increased CDX2 expression along with increased differentiation in the intestinal epithelium of mice.…”
Section: Discussionmentioning
confidence: 88%
“…40 Ablation of Cdx2 in the intestine results in a decrease of mature enterocytes, and loss of goblet, enteroendocrine and Paneth cells. 41 We showed that treatment with βHB or overexpression of ketogenic enzyme HMGCS2 increased CDX2 expression in intestinal cells. Moreover, our results showed that increased ketogenesis resulted in increased CDX2 expression along with increased differentiation in the intestinal epithelium of mice.…”
Section: Discussionmentioning
confidence: 88%
“…Cdx and Brg1 Interact in Vivo-Cdx and SWI-SNF impact intestinal differentiation programs and are required for maintenance of the intestinal stem cell niche (7,11,44). To determine whether Cdx and Brg1 interacted genetically in this context, we assessed intestinal cell differentiation using differential staining for enterocytes and goblet and enteroendocrine cells, comparing control Cdx1 (Fig.…”
Section: Cdx2 and Brg1 Impact The Chromatin Architecture At CDXmentioning
confidence: 99%
“…In the mouse, the three members of this family (Cdx1, Cdx2, and Cdx4) are co-expressed in the caudal embryo in all three germ layers commencing at mid-gastrulation and play overlapping roles in a number of developmental programs, including axial elongation, endoderm specification, and anterior-posterior vertebral patterning (1)(2)(3)(4)(5)(6). Both Cdx1 and Cdx2 are also expressed in the intestinal epithelium throughout life, where they play critical roles in intestinal homeostasis (7)(8)(9)(10)(11) and can function as tumor suppressors (12)(13)(14)(15). Although Cdx members play critical roles in governing gene expression during development and in the adult intestine, little is known about the mechanisms by which Cdx members regulate target gene transcription.…”
mentioning
confidence: 99%
“…CDX2 is required for proper specification of the intestine during development (8) and is considered a master regulator of intestinal identity because its ectopic expression in the stomach or esophagus activates intestine-restricted genes (9,10). In adult mice, absence of CDX2 dysregulates genes involved in terminal cell differentiation, and fatal malnutrition ensues over ϳ3 weeks (11)(12)(13). Simultaneous inactivation of its homolog CDX1 results in nearly complete arrest of intestinal crypt cell proliferation (14).…”
Section: Hnf4a;cdx2 Compound-mutant Intestines Indicated That This Tfmentioning
confidence: 99%